The effectiveness of sun shading device for office tower in Malaysia / Zarina Mat Sapri - Mat Sapri, Zarina (2001)
Shading devices may come in various forms, but the purpose of this application, whether on the internal or external side, are definitely to control direct sun lighting from penetrating inside the building. In a way, the application of shading devices is to control the thermal heat pf the building. Therefore, shading device design must be able to utilise the free energy available form the environment; giving shades to the building as well as controlling the thermal heating. The dissertation shall focus on the nature, function and effectiveness of sun shading device for high-rise building of three case study buildings. The case study buildings: a) KLCC Twin Tower b) Menara Mesiniaga c) Wisma MBSA Based on the visual analysis, it can be said that new development in local economy has contributed to the massive transition development of the shading devices. Besides, the changes in architectural styles in Malaysia, in search of its local or national identity, has long foreseen that shading devices become such a very important building accessories for high-rise building.